A comparative study between low and high pressure pneumopertoneum for the reduction of shoulder- tip pain following laparoscopic cholecystectomy. - Maskey, Sandesh Prakash (2002)
ABSTRACT: Laparoscopic cholecystectomy is the " Golds standard "for the operative treatment of gallstones and now is commonly performed in Nepal. A common problem with this procedure is the postoperative shoulder-tip pain, which occurs frequently following laparoscopic cholecystectomy. Thus the aim of this prospective randomized clinical trial was to evaluate the efficacy of a low-pressure carbon dioxide pneumoperitoneum during laparoscopic surgery in reducing the incidence of postoperative shoulder-tip pain. Methods: A prospective randomized study was done on sixty-four consecutive patients undergoing laparoscopic cholecystectomy. The patients were divided into low-pressure (group A) and high-pressure (group B) laparoscopic cholecystectomy groups. Patients in group A (n=34.) underwent laparoscopic cholecystectomy with 9-10mmHg carbon dioxide pneumoperitoneum during most of the operation and those in group B (n=344) had laparoscopic cholecystectomy with 13-14 mmHg pneumoperitoneum. Shoulder-tip pain was recorded on a verbal rating pain scoring system on the evening of the operation day, in the morning of the first postoperative day and in the morning of the second postoperative day. Results: The low-pressure pneumoperitoneum did not increase the duration of surgery siginifacantly. There were no significant intraoperative or postoperative complications in either group. Six patients (18.2%) in group A and ten patients (30.3%) in - group B complained of shoulder-tip pain in the morning of the first postoperative day. (P<0.0024). Nine (27.2%) patients in group A and twelve patients. (36.4%) in-group B complained of shoulder pain in the morning of the second postoperative day. The intensity of shoulder-tip pain on the morning of the first postoperative day and second postoperative day and second postoperative day was lower in the low-pressure laparoscopic cholecystectomy group. Postoperative analgesia requirements were also significantly lower in the low-pressure laparoscopic cholecystectom group. (P<0.0004) In conclusion, a carbon dioxide pneumoperitineum pressure of 9-10 mmHg can be used to perform laparoscopic surgery without compromising the suirgery, reduces both the frequency and intensity of shoulder-tip pain. Postoperative analgesia requirements as reflected by the number of doses of doses of narcotic analgesics were also significantly lower.